Ethnicity, identity and nationalism: The sandinista-miskitu encounter, 1981-1987 / Marissa Olivares - Olivares, Marissa (1998)
Since colonial time the culture, identity and history of the Miskitu1 people -along with the Sumu-Mayangna, Rama, Garifona and Creo les of the Eastern Caribbean coast of Nicaragua-2 have emerged along a different path from that of the rest of Nicaragua. In particular, this difference has been used by the Sandinistas to construct the Miskitu as less than legitimate within the mainstream of the Nicaraguan nation and state. This characterization is also reflected in the mainstream, historical and anthropological works, integrationist policies of the 1980s. Although this strategy has been cast as providing the Miskitu with more autonomy, questions can be raised about its placing them in a position to be controlled by the norms of nationhood and citizenry. It can be argued that this orientation on the part of the Sandinista state is part of the colonial legacy that promotes the culture and identity of mestizaje over the Miskitu culture and identity and seeks to; which differs from that of the rest of society emerges primarily through the discourses surrounding the early 1980's movement to integrate them within the core of the nation and in the work of mainstream historians and anthropologists. These treatments of the Miskitu people painted a picture of a backward people, living in the past, unable to develop a complex society reflective of modem values. Furthermore, according to the mainstream discourses the nation has been constructed as a homogeneous mestizo, Catholic, and Spanish-speaking community, leaving little or no room for the other non¬mestizo, non-Spanish and non-Catholic faces of the Miskitu people. Within the Sandinista discourse on nation, nationalism and nationhood, the Miskitu people are defined as ethnic minorities reminiscences of a colonial past; the Sandinista state have argued that the Miskitu must be brought into the present to be integrated into the modern nation, to adopt the modern nation's norms, rules, culture and history; In this study I have investigated how the ethnic question that emerged in the 1980s has been characterized and constructed within the Sandinista discourse on nation, nationalism and nationhood. I focused in particular on how the ethnic question and the national question become intertwined and examined the tensions between them. In order to provide the necessary contextual background for interpreting; developments taking place in the early 1980s, I have examined the unfolding of particular periods in history, such as the period of the Anglo-Spanish struggle for the Miskitu coast up until the "Reincorporation" of 1894. And the events surrounding the Miskitu uprising of the 1980s.